Movement tortuosity and speed reveal the trade-offs of crop raiding for African elephants. (October 2020) - Troup, Georgia; Doran, Bruce; Au, Jessie; King, Lucy E.; Douglas-Hamilton, Iain; Heinsohn, Robert
Abstract : Animals living in heterogeneous landscapes are often faced with making a trade-off between maximizing foraging success and avoiding risk. Using high-resolution GPS-tracking data, this study explored the fine-scale movement patterns and risk sensitivity of crop-raiding African elephants, Loxodonta africana, in the anthropogenic landscape of Tsavo, Kenya. We analysed patterns in the speed and tortuosity of elephant movements over the 24 h surrounding crop-raiding events and compared them with those of nonraiding elephants during corresponding periods. Crop-raiding elephants moved faster and straighter (less tortuously) with closer temporal proximity to farmland, which we argue reflects their increased intensity of risk avoidance behaviours in response to approaching humans. Once inside farmland, elephants appeared to reduce movements associated with risk avoidance to forage intensively on crops, decreasing their speed and reducing the likelihood of moving in straight lines while crop raiding. These results highlight trade-offs in the fine-scale movement patterns of elephants living in anthropogenic landscapes with differing levels of habitat quality and exposure to humans, providing new insight into how they perceive the risks associated with crop raiding. Highlights: Elephants move faster and straighter with closer temporal proximity to farmland. Inside farmland, elephants decrease speed and likelihood of moving straight. Elephants may consider the nutritional gain from crop raiding to outweigh the risks.